2008
DOI: 10.1002/pmic.200700969
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometry‐assisted purification and proteomic analysis of the corticotropes dense‐core secretory granules

Abstract: The field of organellar proteomics has emerged as an attempt to minimize the complexity of the proteomics data obtained from whole cell and tissue extracts while maximizing the resolution on the protein composition of a single subcellular compartment. Standard methods involve lengthy density-based gradient and/or immunoaffinity purification steps followed by extraction, onedimensional or two-dimensional gel electrophoresis, gel staining, in-gel tryptic digestion and protein identification by mass spectrometry.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 63 publications
0
40
0
Order By: Relevance
“…However, among them, the only membrane protein able to accumulate calcium in the vesicles was a sodium/potassium/calcium exchanger. Previous studies in pancreatic zymogen granules [45] (371 proteins identified) and corticotropes dense-core secretory granules [46] (150 proteins identified) had not identified any protein related with Ca 2+ accumulation. Instead, a proteomic study that identified 270 proteins in secretory vesicles from insulinoma NIT-1 cells showed the presence of SERCA2 in the membrane of the vesicles [47], but another study in the insulin-secreting cell line INS-1E that identified 150 vesicular proteins failed to find any Ca 2+ transport protein [48].…”
Section: Mechanisms Of Ca 2+ Accumulation In the Secretory Granulesmentioning
confidence: 84%
See 1 more Smart Citation
“…However, among them, the only membrane protein able to accumulate calcium in the vesicles was a sodium/potassium/calcium exchanger. Previous studies in pancreatic zymogen granules [45] (371 proteins identified) and corticotropes dense-core secretory granules [46] (150 proteins identified) had not identified any protein related with Ca 2+ accumulation. Instead, a proteomic study that identified 270 proteins in secretory vesicles from insulinoma NIT-1 cells showed the presence of SERCA2 in the membrane of the vesicles [47], but another study in the insulin-secreting cell line INS-1E that identified 150 vesicular proteins failed to find any Ca 2+ transport protein [48].…”
Section: Mechanisms Of Ca 2+ Accumulation In the Secretory Granulesmentioning
confidence: 84%
“…None of the proteomic studies made up to date has detected the presence of InsP 3 R in the secretory granules of chromaffin [44], insulin [47,48], zymogen [45] or corticotrope granules [46]. Instead, the largest study [44] found in chromaffin granules the presence of ryanodine receptors together with several types of Ca 2+ channels (voltagedependent and transient receptor potential).…”
Section: Mechanisms Of Ca 2+ Release From the Secretory Granulesmentioning
confidence: 99%
“…It is also possible to use flow cytometry to isolate secretory granules, as shown by the isolation procedure used for the corticotropes dense-core secretory granules (Gauthier et al, 2008). In this study, the authors first generated an AtT-20 stable cell line that expressed the green fluorescent protein PHMmGFP.…”
Section: A Isolation Of Regulated Secretory Organellesmentioning
confidence: 99%
“…It allows a very high mass accuracy, dynamic range and resolution power (Makarov et al, 2006a,b). An LTQ Orbitrap mass spectrometer has been recently used for the proteomic analysis of corticotropes dense-core secretory granules (Gauthier et al, 2008).…”
Section: E Identification Of Secretory Organelles Proteins With Massmentioning
confidence: 99%
“…Pellets were then resuspended in lysis buffer and sonicated. The supernatant was transferred to new tubes after centrifugation at 1500 rpm for 10 min and sorted by flow cytometry as described previously (35). The enrichment of GFP puncta was confirmed by microscopic observation.…”
Section: Methodsmentioning
confidence: 99%